PERLINDUNGAN KONSUMEN INDUSTRI KONSER DI INDONESIA: KAJIAN IMPLEMENTASI UU PERLINDUNGAN KONSUMEN - Husni Kurniawati; Salma Nur Hanifah (MAGISTRA Law Review, 2025)
The rapid growth of the concert industry in Indonesia has not been matched by adequate consumer protection practices. Consumers often face issues such as ticket fraud, sudden cancellations without compensation, changes in event venues, and misleading promotional content. This research identifies the gap between legal consumer protection frameworks and their actual implementation in the concert sector. Using a normative juridical method with a prescriptive-analytical approach, this study analyzes how consumer rights are neglected in transactions involving concert services. The findings reveal that many organizers fail to act transparently or responsibly, leading to significant material and immaterial losses for consumers. Moreover, existing complaint mechanisms remain ineffective and lack enforcement power. The study implies an urgent need for specific regulations to govern concert organization practices, including refund procedures, clear communication, and fair dispute resolution. Strengthening institutional capacity and regulatory oversight is essential to ensure accountability and safeguard consumer interests in the entertainment industry.